Biodiversity and distribution of cyanobacteria at Dronning Maud Land, East Antartica - Singh, Shiv Mohan; Singh, Purnima; Thajuddin, Nooruddin (Universidad de Málaga, Servicio de Publicaciones, 2008)
Biodiversity and distribution of cyanobacteria at Dronning Maud Land, East Antarctica.The current study describes the biodiversity and distribution of cyanobacteria from the natural habitats of Schirmacher land, East Antarctica surveyed during 23rd Indian Antarctic Expedition (20032004). Cyanobacteria were mapped using the Global Positioning System (GPS). A total of 109 species (91 species were non-heterocystous and 18 species were heterocystous) from 30 genera and 9 families were recorded; 67, 86 and 14 species of cyanobacteria were identified at altitudes of sea level >100 m, 101150 m and 398461 m, respectively. The relative frequency and relative density of cyanobacterial populations in the microbial mats showed that 11 species from 8 genera were abundant and 6 species (Phormidium angustissimum, P. tenue, P. uncinatum Schizothrix vaginata, Nostoc kihlmanii and Plectonema terebrans) could be considered as dominant species in the study area.

Biodiversidad y distribución de las cianobacterias de Dronning Maud Land, Antártida Oriental. En este estudio se describe la biodiversidad y distribución de las cianobacterias presentes en los hábitats naturales de Schirmacher, Antártida Oriental, muestreados durante la 23ª Expedición India a la Antártida (2003-2004). Las muestras de cianobacterias fueron georreferenciadas mediante un GPS. Se identificaron 109 especies (91 no heterocistadas y 18 provistas de heterocistes) de 30 géneros y 9 familias; en los tramos de altitud sobre el nivel del mar >100 m, 101-150 m y 398-461 m se detectaron 67, 86 y 14 especies, respectivamente. La frecuencia y densidad relativas de las poblaciones de cianobacterias en los tapices microbianos mostraron que 11 especies de 8 géneros eran abundantes y que 6 especies (Phormidium angustissimum, P. tenue, P. uncinatum, Schizothrix vaginata, Nostoc kihlmanii y Plectonema terebrans) se pueden considerar como dominantes en el área de estudio.